2012
DOI: 10.1007/s11606-012-2271-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Completion of Laboratory Tests to Monitor Medication Therapy: A Mixed-Methods Study

Abstract: BACKGROUND:Little is known about the contribution of patient behavior to incomplete laboratory monitoring, and the reasons for patient non-completion of ordered laboratory tests remain unclear. OBJECTIVE: To describe factors, including patientreported reasons, associated with non-completion of ordered laboratory tests. DESIGN: Mixed-Methods study including a quantitative assessment of the frequency of patient completion of ordered monitoring tests combined with qualitative, semi-structured, patient interviews.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Finally, previous studies on primary care providers’ perceived enablers and barriers to ordering laboratory tests in general have also identified that a barrier is patients not completing the laboratory test [ 37 , 40 ]. A mixed methods study on patient perceived barriers to not completing a laboratory test after initiating a new medication that required monitoring included barriers of forgetting or competing demands [ 41 ]. Since our study only included the primary care provider perspective, we cannot make any conclusions about the applicability of these patient-specified barriers to completing a repeat serum creatinine test.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous studies on primary care providers’ perceived enablers and barriers to ordering laboratory tests in general have also identified that a barrier is patients not completing the laboratory test [ 37 , 40 ]. A mixed methods study on patient perceived barriers to not completing a laboratory test after initiating a new medication that required monitoring included barriers of forgetting or competing demands [ 41 ]. Since our study only included the primary care provider perspective, we cannot make any conclusions about the applicability of these patient-specified barriers to completing a repeat serum creatinine test.…”
Section: Discussionmentioning
confidence: 99%
“…Better efficiency and appropriateness in prescribing practice could be achieved by addressing the over- or under-utilisation of drugs. It was shown that prescribed medications are often taken for long periods beyond the point when they are needed and around 30% of drugs are abandoned by patients [ 22 25 ]. Major NHS savings could also be generated by using treatments that are most cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of diagnostic laboratory testing increases with age, since the likelihood of comorbidity and polypharmacy also increase with age. Older patients tend to have more contact with their healthcare providers, and thus are more likely to complete laboratory testing than those younger in age [ 47 ]. Polypharmacy further increases the risk of adverse drug interactions; therefore, patients on high-risk medications, and also those on thiazide diuretics, are significantly more likely to complete regular testing as well [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%